SPECIFIC FEATURES OF THE IDEA OF TOLERANCE IN DEVELOPING THE STABILIZATION OF SOCIAL LIFE IN SOCIETY (Multidisciplinary Journal of Science and Technology, 2026)
This article reflects the specific features of the idea of ​​tolerance in stabilizing the social life of society, its culture, universal values, lifestyle, traditions, the thoughts of Western researchers of the 20th century, and social processes associated with rich spiritual and historical processes.